COUNSELING REGARDING EXCLUSIVE BREASTFEEDING TO BABIES NEWBORN FIRST THREE DAYS OF BIRTH - sembiring, bungamari; Lubis, Fithri Handayani (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Increasing the role that families, communities, regional governments, and the government play in the promotion of exclusive breastfeeding is one of the goals of Government Regulation No. 33 of 2012, which was issued in reference to the topic of exclusive breastfeeding. Because the support of the husband will produce a sense of comfort in the mother, which will effect the production of breast milk and improve the mother's enthusiasm and comfort in nursing, the support of the family, particularly the husband, can be a determining factor in whether or not breastfeeding is successful. Research conducted by the World Health Organization (WHO) in the year 2020 suggests that all infants should be breastfed exclusively until they reach the age of six months. This is due to the fact that breastmilk is considered to be the food that provides the highest nutritional value for infants. The findings of this study indicate that only 41% of all infants around the world are exclusively breastfed. The World Health Organization (WHO) has set a goal to increase the percentage of infants who are exclusively breastfed by at least fifty percent by the year 2025. Breastfeeding or the administration of breast milk (ASI) should be initiated as soon as possible following the birth of the child. This practice is generally referred to as Early Breastfeeding Initiation (IMD). After giving birth, the mother should immediately begin breastfeeding the infant for a maximum of half an hour. For the baby to receive an adequate amount of breast milk, this is of utmost importance. It is possible that giving the baby anything other than breast milk, even water, could make the infant sick and reduce the amount of milk that the mother produces. This is due to the fact that the amount of milk that the mother produces is dependent on the amount of milk that the baby sucking on the breast. Even if the infant is given another drink or water, he will not feel hungry, and as a result, he will not breastfeed. When it comes to the success of exclusive breastfeeding in newborn babies during the first three days of their lives, the variable that is most closely associated to this success is family support. In the first three days after birth, the mother will experience a number of conditions that can make it difficult for her to give her baby exclusive breast milk. These conditions include the mother's breast milk that is difficult to come out, babies that are fussy, and the mother's adjustment to postpartum physical and psychological conditions. Therefore, during these times, the mother will require support from her family in order to be able to strengthen her and emphasize the significance of exclusive breastfeeding, particularly during the first three days after birth.